Analisis Rasio Profitabilitas Dalam Mengukur Kinerja Keuangan Pada Bank Syariah Mandiri (Penelitian Tentang Return On Asset, Return on Equity, Gross profit margin dan Net Profit Margin pada Tahun 2015–2019) - Diana Novita; Jalaludin Jalaludin; Moch. Cayho Sucipto (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2022)
Financial performance is a description of the financial condition of a company in a certain period which is analyzed with financial analysis tools. In assessing the company's financial performance, usually the measure used is the ratio. This research is motivated by the results of the profit data of Bank Syariah Mandiri which decreased in 2016, while assets and operating income from 2015 to 2019 the bank experienced a significant increase, therefore the authors tried to measure the financial performance of independent Islamic banks for 5 years. year. The purpose of this study was to find out and analyze how the financial performance of Bank Syariah Mandiri during 2017-2019. The researcher analyzes the financial performance of independent Islamic banks using profitability ratios based on Return On Assets, Return on Equity, Gross Profit Margin, and Net Profit Margin, after the analysis will show the condition of the Islamic Bank's financial performance. This study uses a quantitative descriptive approach by using the measurement of profitability ratios. The data studied are in the form of financial statements of Bank Syariah Mandiri from 2015 to 2019. Based on the results of the analysis, it is concluded that the financial performance of Bank Syariah Mandiri for 5 years from 2015-2019 based on ROA is considered unhealthy, this is based on the results of the average calculation ROA for 5 years is 0.79%, below the ROA standard of 1.25%. The financial performance of Bank Syariah Mandiri for 5 years from 2015-2019 based on ROE is considered unhealthy, this is based on the results of the calculation of the average ROE for 5 years, which is 8.88%, below the ROE standard of 12.5%. The financial performance of Bank Syariah Mandiri for 5 years from 2015-2019 based on GPM is considered unhealthy, this is based on the results of the calculation of the average GPM for 5 years, which is 8.35%, below the GPM standard of 10%. The financial performance of Bank Syariah Mandiri for 5 years from 2015-2019 based on the NPM is considered healthy, this is based on the results of the calculation of the average NPM for 5 years which is 7.54%, which is in a position above the NPM standard of 5%.